Статистические критерии при нормировании вибрации газоперекачивающих агрегатов - Игуменцев, Е. А.; Прокопенко, Е. А.; Марчук, Я. С. (Національний технічний університет "Харківський політехнічний інститут", 2004)
Разработана статистическая модель нормирования общего уровня вибрации газоперекачивающих агрегатов. Предельные уровни вибрации, при которых ремонт агрегатов не требуется, установлены посредством критерия Неймана-Пирсона. Получена плотность распределения вероятности общего уровня случайной вибрации агрегатов, рассчитаны предельные уровни виброскорости корпусов подшипников ГПА-10. В качестве предельных значений использованы моменты первого и второго порядка полученного распределения.

The statistical model of vibration of a total level gas transporting units is developed. The marginal levels of vibrations, at which the repair of units is not required, are established by means of Newman-Pierson criterion. Density probability distribution of the general level casual vibration of units is received, the marginal vibration velocity levels of cases of bearings GPA-10 are designed. As limiting meanings the moments of the first and second order of the received distribution are used.
Statistical criteria at setting of vibration norms in gas transporting units
Keywords: газоперекачивающий агрегат; вибрации; критерий Неймана-Пирсона; виброскорость; turbine; vibration; norms; probability; failure